1991
DOI: 10.1002/em.2850180109
|View full text |Cite
|
Sign up to set email alerts
|

Chemical mutagenesis at the thymidine kinase locus in L5178Y mouse lymphoma cells: Results for 31 coded compounds in the national toxicology program

Abstract: Experimental data from the testing of 31 chemicals for mutagenicity at the TK locus in L5178Y mouse lymphoma cells are presented and evaluated. If mutagenic activity was not obtained for the chemical added to suspension cultures for 4 hr, then the testing was repeated in the presence of hepatic S9 mix prepared from Aroclor 1254-induced male Fischer 344 rats. Multiple trials were performed for each chemical, and mutagenic treatments were analyzed for the induction of small and large mutant colony populations. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(36 citation statements)
references
References 18 publications
0
36
0
Order By: Relevance
“…Technical deficiencies in the conduct of the in vitro mammalian cell mouse lymphoma assay (no colony sizing) limit the usefulness of the in vitro mammalian data (16). In vitro gross chromosome aberration analysis using Chinese hamster ovary cells found TCE to be negative both with and without exogenous activation (17).…”
Section: Trichloroethylenementioning
confidence: 99%
“…Technical deficiencies in the conduct of the in vitro mammalian cell mouse lymphoma assay (no colony sizing) limit the usefulness of the in vitro mammalian data (16). In vitro gross chromosome aberration analysis using Chinese hamster ovary cells found TCE to be negative both with and without exogenous activation (17).…”
Section: Trichloroethylenementioning
confidence: 99%
“…Among all the experiments, only one dose in lab B with S9 mix showed a statistically significant response in a pair-wise comparison. The mutagenicity of tetrachloroethane in the MLA has been debated and discrepant results were obtained in two experiments by the NTP; McGregor et al (1988b) reported a positive result in the presence and absence of S9 mix, while Myhr and Caspary (1991) reported negative results under both conditions.…”
Section: -Fluorouracil (5fu): Positive (-S9/ϩs9mentioning
confidence: 99%
“…Therefore, this chemical was judged inconclusive with and without S9 mix. NTP reported that bisphenol A was non-mutagenic in the MLA (Ivett et al, 1989;Myhr and Caspary, 1991). p-t-Butylphenol: negative (-S9/ϩS9: -/-).…”
Section: -Fluorouracil (5fu): Positive (-S9/ϩs9mentioning
confidence: 99%
“…With the same substance equivocal results in an in vivo host mediated mutation assay were observed at high dose levels (Food and Drug Research Laboratories, Inc., 1975) and negative results in several Ames tests, a TK+/-mouse lymphoma assay (Myhr and Caspary, 1991), sister chromatid exchange (SCE) tests in Chinese hamster ovary (CHO) cells (Ivett et al, 1989) and human lymphocytes (Murthy et al, 1991), and chromosomal aberration assays with human embryonic lung cells (Food and Drug Research Laboratories, Inc., 1975), human lymphocytes (Murthy et al, 1991) and CHO cells (Ivett et al, 1989). Negative results were also reported in two in vivo micronucleus (Shelby et al, 1993) and chromosomal aberration assays (Food and Drug Research Laboratories, Inc., 1975).…”
Section: Genotoxicity Studiesmentioning
confidence: 99%